Trends in burden of falls among children aged 0–14 years in China from 1990–2021 and prediction to 2030 - Xiong, Huali; Liu, Daiqiang; Yuan, Xiaoqin; Yang, Yue (Frontiers in Public Health, 2025)
BackgroundAlthough falls are the major cause of non-fatal injuries and preventable deaths among Chinese children, comprehensive assessments of the temporal trends in the burden of falls among children aged 0–14 years in China remain scarce. To address this gap, we quantified national and temporal trends in burden of falls among children aged 0–14 years from 1990 to 2021 and projected future trends through 2030.MethodsThe current study used data from the Global Burden of Disease Study 2021 (GBD2021), we extracted crude incidence, mortality, years of life lost (YLLs), years lived with disability (YLDs), and disability-adjusted life years (DALYs) attributable to falls along with their corresponding absolute counts for Chinese children aged 0–14 years during 1990–2021. All metrics were stratified by sex and 5-year age group. Age-standardized rates (ASRs), including age-standardized incidence rate (ASIR), age-standardized mortality rate (ASMR), age-standardized YLLs rate, age-standardized YLDs rate, and age-standardized DALY rate (ASDR) for children aged 0–14 years, were recalculated using the World Health Organization’s standard population. Temporal trends were assessed with Joinpoint regression model to compute average annual percentage changes (AAPCs). Finally, autoregressive integrated moving average (ARIMA) models were developed to project ASRs for children aged 0–14 years through 2030.ResultsBetween 1990 and 2021, children aged 0–14 years experienced 163,769,426 incident cases and 255,840 deaths, resulting in a total of 25,085,796 DALYs. The ASIR, ASMR, age-standardized YLLs rate, age-standardized YLDs rate, and ASDR all demonstrated a downward trends with AAPCs of −0.34% (95%CI: −0.39% to −0.28%, P<0.001), −4.18% (95%CI: −4.37% to −4.06%, p < 0.001), −4.24% (95%CI: −4.43% to −4.11%, p < 0.001), −1.16% (95%CI: −1.22% to −1.11%, p < 0.001), −3.68% (95%CI: −3.80% to −3.57%, p < 0.001), respectively. In stratified analysis, similar downward trends were observed aross both sexes and age group of 0–4 years, 5–9 years and 10–14 years. Notably, upward trends were observed in the ASIR from 2010 to 2021 and the age-standardized YLDs rate from 2010 to 2021. Children aged 10–14 years exhibited an upward trend in incidence rate 1990 to 2021. Predictions shows the incidence among children aged 0–4 years is projected to rise, and an increase in YLDs is anticipated among children in both the 0–4 years and 5–9 years age groups.ConclusionThe burden of falls remains a major public challenge among children aged 0–14 years, although its burden at the national level showed a downward trend from 1990 to 2021. The age-standardized YLDs rate among males, the incidence among children aged 0–4 years and the YLDs among children aged 0–9 years are projected to increase from 2022 to 2030. These findings suggest that mandatory implementation of age-specific fall-prevention protocols in kindergartens and primary schools nationwide and expand the coverage of injury surveillance and implement it nationwide.